Masalah Penerjemahan Kolokasi dalam Tafsir Fi Zilal al-Qur’an - Saifullah Kamalie (Universitas Darussalam Gontor, 2013)
Collocation is a universal linguistic phenomenon and has become the research topic of linguists, dictionary experts, language pedagogy experts, and also those who are involved in the ﬁeld of translation. According to translation experts, a good translation is a translation that looks not like a translation. One of factors that cause the readers knowing and feeling that a translation is a translation is that the translator fails to identify a combination of a number of lexical items as a collocation. The ability to identify a collocation in the original text is the initial capital for a successful translation. In general, the translator is not a graduate from translation department of literature faculty. The Arabic language skills they have may already be sufﬁcient. However, to become a good translator is not enough to just master the source language, but also should master the target language. It must be admitted, that during this time, learning Arabic is mainly concentrated on grammar alone while collocation is still a 'rare' or 'weird' thing in the eyes of the Arabic language learners. Teaching of Arabic language by giving an attention to the collocation will familiarize learners to use Arabic language appropriately like native speakers do it. If the translators know collocation and succeed to identify it in doing analysis on the source text, the result of translation will be free from the literal translation and the rigid structure of the language.